Smart Sensors and Devices in Artificial Intelligence - Dan Zhang; Bin Wei (Sensors, 2020)
As stated in the Special Issue call, “sensors are eyes or/and ears of an intelligent system, such as Unmanned Aerial Vehicle (UAV), Automated Guided Vehicle (AGV) and robots [...]